Intelligent Polymer‐Based Bioinspired Actuators: From Monofunction to Multifunction. (23rd August 2020) - Cui, Huanqing; Zhao, Qilong; Zhang, Li; Du, Xuemin
Abstract : In nature, creatures possess a variety of actuation behaviors such as dynamic modulations of their configurations, colors, and positions, which provide inexhaustible inspirations for the design and construction of bioinspired actuators to conduct tasks in dynamic environments. With the assistance of remarkable advances in materials especially stimuli–responsive polymers, the bioinspired actuators have been remarkably evolving from monofunction of only actuation to multifunction with integrating sensing, reporting, and locomotion capabilities, which offer possibilities to make bioinspired actuators intelligent via providing feedback and obtaining autonomous abilities in mission execution. The intelligence of the bioinspired actuators by integrating multiple functions also significantly broadens their applications, particularly in biomedical and robotic fields that usually involve dynamic and complicated circumstances. Herein, the evolution of the intelligent polymer‐based bioinspired actuators from monofunction to multifunction is introduced, which focuses on the design strategies for each of them with gradually updating capabilities and their representative applications in diverse biomedical and robotic areas. Future challenges for achieving the enhanced intelligence of the bioinspired actuators on a par with the living creatures are finally discussed, which shall be addressed through extensive innovations of materials and systems. Abstract : Herein, the evolution of the intelligent polymer‐based bioinspired actuators from monofunction to multifunction is introduced, which focuses on the design strategies with gradually updating capabilities and their representative applications in diverse biomedical and robotic areas. Future challenges for achieving the enhanced intelligence of the bioinspired actuators on a par with the living creatures are also discussed.